1993
DOI: 10.1002/app.1993.070480117
|View full text |Cite
|
Sign up to set email alerts
|

The effects of γ irradiation on toughening mechanisms in rubber‐modified polymers

Abstract: SYNOPSISHigh-impact polystyrene (HIPS) and acrylonitrile butadiene styrene ( ABS ) have been subject to y irradiation in doses up to 20 and 12.5 Mrad, respectively. During tensile testing, both longitudinal extension and lateral contraction were simultaneously measured, allowing determination of volume strain, and from this to identify the relative contributions of crazing and shear yielding to the tensile deformation process. Both materials show a doserelated increase in the strain at which crazing commences,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
2
2
0
Order By: Relevance
“…Our results are consistent with the suggestions of Birkinshaw et al 36 and Bucknall and coworkers33 who proposed that the two toughening mechanisms in ABS have different rates of response. At higher rates of strain and at relatively high stresses, crazing and crack fibrillation are more important; and a t the lower strain rates encountered in the tensile tests, shear yielding can also play an effective toughening role.…”
Section: No Definite Trend Between Tearing Modulus ( T I M )supporting
confidence: 93%
“…Our results are consistent with the suggestions of Birkinshaw et al 36 and Bucknall and coworkers33 who proposed that the two toughening mechanisms in ABS have different rates of response. At higher rates of strain and at relatively high stresses, crazing and crack fibrillation are more important; and a t the lower strain rates encountered in the tensile tests, shear yielding can also play an effective toughening role.…”
Section: No Definite Trend Between Tearing Modulus ( T I M )supporting
confidence: 93%
“…In the case of small-sized particles, crazes initiate from the equator of the particle and lie in a plane perpendicular to the applied stress axis, and the ''activity'' of large particles is far higher than that of the small ones [42]. The results are also in good agreement with the previous investigations [43,44]. It is shown that the different deformation rates could mainly produce two toughening mechanisms in ABS.…”
Section: Fractographysupporting
confidence: 88%
“…Previous studies of the effects of γ‐irradiation on HIPS and PS have been made by Birkinshaw, Buggy, and coworkers,19, 20 who measured changes in molecular weight, tensile stress–strain behavior, and impact strength. They showed that only minor changes occur in PS, whereas the properties of HIPS alter dramatically.…”
Section: Introductionmentioning
confidence: 99%